Improving Hospital Services through the Implementation of Health Tourism Innovations at the Moh. Hatta Brain Hospital, Bukittinggi City - Getha Sekartadji; Hendri Koeswara; Desna Aromatica (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to clarify what efforts are being made to improve the quality of hospital services through the implementation of health tourism in Bukittinggi City Hospital. The research method used in this study is a qualitative descriptive research method. Qualitative research is a method of collecting data using words and pictures rather than numbers. Based on the results of the research, the health tourism program is a special program that regulates the journey of a sick patient in a lying condition starting from home to the destination hospital to returning home by providing tour packages. The challenges of implementing this program are from internal factors, including administration and management which still need to be addressed, as well as the lack of mastery of English if there are patients who are foreign nationals.